Interfaith Dialogue Format in Fostering Peace on Instagram: Indonesia Celebrates Diversity - Edward Hiroshi Tandawidjaja; Inri Inggrit Indrayani; Astri Yogatama (Journal of Content and Engagement, 2025)
This research aims to examine the peace dialogue format in fostering harmony on Instagram Indonesia Merayakan Perbedaan (IMP). This research uses descriptive quantitative research, where this study aims to examine the use of dialogue formats in fostering harmony on the Instagram social media platform IMP. The researcher found three indicators used in the study, namely cognitive, affective, and collaborative. In each indicator, there are themes raised by the researchers to classify each post. The most frequently appearing theme in the cognitive indicator is the theme of knowledge of differences and similarities. The most frequently appearing affective theme is the theme of togetherness. The most prominent collaborative theme is the theme of collaboration in building the nation. The result of this research is that, in building peace on Instagram IMP, the cognitive indicator is the most widely used indicator. In conclusion, the cognitive aspect is useful for building a dialogue of harmony among religious communities and cultures in Indonesia, especially on the theme of understanding differences and similarities.